CFD Simulation Analysis of Non-Premixed Combustion using a Novel AxialRadial Combined Swirler for Emission Reduction Enhancement - Nor Afzanizam Samiran, Nor Afzanizam Samiran; Khalil Firdaus Abu Mansor, Khalil Firdaus Abu Mansor; Razlin Abd Rashid, Razlin Abd Rashid; Muhammad Suhail Sahul Hamid, Muhammad Suhail Sahul Hamid (semarak ilmu, 2023)
Combustion industries for many decades dealing with the issues in reducing the emissions without affecting the performance of combustion. The present study aims to investigate the performance of swirler mechanism which combining between both axial and radial types to reduce emissions and increase the mixing process via the nonpremixed method. Each of axial and radial swirler consisted with 8 blades vane. Swirl angle for radial swirler is 35° and inclination angle for axial swirler is 15°. The swirler is designed using Solidworks software package and CFD analysis was then performed using ANSYS Fluent software package. The fuel used is liquefied petroleum gas (LPG) gas which contained 30% propane and 70% butane. The turbulence model standard kepsilon was used in this study. The result found that the combined swirler was capable to reduce CO emission as the complete reaction into CO2 component was higher. This is due to the broader region of temperature and higher velocity magnitude produced by the combined swirler. However, the maximum temperature result for axial swirler was higher than the combined swirler. As a recommendation, the inclination blade angle in the axial swirler of the combined swirler should be increased to increase the temperature value.